Air‐In‐Water Emulsion Solely Stabilized by Gelatin Methacryloyl and Templating for Macroporous Nanocomposite Hydrogels. Issue 9 (6th May 2019) - Liu, Sa; Jin, Min; Chen, Yunhua; Teng, Lijing; Qi, Dawei; Ren, Li
Abstract : Front Cover : In article number1800500 by Yunhua Chen, Li Ren, and co‐workers, air‐in‐water emulsions solely stabilized by gelatin methacryloyl are developed and the emulsion templates are utilized to create promising macroporous nanocomposite hydrogels. Promising mechanical reinforcement, cell proliferation, and significant increase of alkaline phosphatase activity are shown in hydrogels incorporated with Laponite clay, indicating the capabilities of promoting osteogenesis of the hydrogels in the absence of osteoinductive factors.